CD14 and CD16 expression in noninfectious granulomatous skin diseases. Issue 1 (8th January 2020) - Ito, Yuta; Kitakawa, Maki; Koshikawa, Sachiko; Watanabe, Hideaki; Sueki, Hirohiko
Abstract: Objectives: Peripheral blood monocytes are categorized as classical (CD14 ++ /CD16 − ) or nonclassical (CD14 − /CD16 +  and CD14 + /CD16 + ) based on their CD14 expression and CD16 expression. Maturation of classical monocytes produces CD14 + /CD16 + macrophages. Our aim was to clarify the in vivo distribution of CD14 and C16 monocytes/macrophages in three granulomatous skin diseases—sarcoidosis, granuloma annulare, and lupus miliaris disseminatus faciei. Methods: CD14 and CD16 immunohistochemistry, and CD14/CD16, CD16/CD11c, CD16/CD68, and CD16/factor XIIIa dual labeling were performed in tissues sampled from three cases of sarcoidosis, four cases of granuloma annulare, and three cases of lupus miliaris disseminatus faciei. Results: The main infiltrating cell types were CD14 + /CD16 + and CD14 − /CD16 ++ macrophages. A small number of CD14 + /CD16 − macrophages localized along the granuloma periphery. Dual immunofluorescence showed that CD16 + overlapped the most with CD68 + cells, partially overlapped with CD11c + cells, and did not overlap with FXIIIa + cells. Conclusions: Inflammatory granulomatous skin diseases are characterized by CD16 +, mature and inflammatory macrophages; some of which are in the process of maturation. Abstract : The main infiltrating cell types were CD14 + /CD16 + and CD14 − /CD16 ++ macrophages. A small number of CD14 + /CD16 − macrophages localized along the granuloma periphery. Inflammatory granulomatous skin diseases are characterized by CD16 +, mature, and inflammatory macrophages; some of which are in the process of maturation.